Field notes contributed by Pam Allen and Reid I. Allen, spring 1992 - Allen, Pamet al; Allen, Reid I.et al (1992)
List of birds and locations contributed by Pam Allen and Reid I. Allen with observers Eloise Armstrong, Eugene Armstrong, Ann Johnson, Thomas H. Kent and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1992. Plustek - flatbed